A QUALITATIVE STUDY OF THE NOVICE PRINCIPALS' PROBLEMS IN THE SCHOOL MANAGEMENT PROCESS AND SOLUTIONS - Karakose, Turgut; Yirci, Ramazan; Kocabas, Ibrahim (ISOSS PUBL, 2014)
The aim of this study is to determine the problems that school principals face during the first year of their job and again find solutions for these problems according to their perspective. Qualitative research method was used in the development of the study and the data was analyzed through the content analysis method. The problems that the school principals faced was grouped under five categories according to the collected data. The most outstanding problem among them was related to the school facilities. Then the problems concerning school stakeholders, education policies, administrative issues and financial issues came respectively. School principals offered various solutions for these problems. In order to solve the problems, principals suggested that the school facilities should be improved, the school budget should be increased, training programs should be set for principal candidates, principals should be given the opportunity to take master's degree and formal mentoring programs should be arranged for principal candidates.
Keywords: Qualitative study; novice principals; school management; problems; educational system; LEADERSHIP; TEACHERS; TOP; Mathematics